Synthesis of polypyrrole – chitosan magnetic nanocomposite for the removal of carbamazepine from wastewater: Adsorption isotherm and kinetic study. Issue 4 (August 2021) - Nezhadali, Azizollah; Koushali, Sara Easapour; Divsar, Faten
Abstract: A polypyrrole–chitosan–Fe3 O4 magnetic nanocomposite (PPy–CS–Fe3 O4 MNC) was prepared by in situ coprecipitation of iron salts in the presence of chitosan followed by chemical oxidative polymerization of pyrrole on the magnetic chitosan. Afterward, the nanocomposite was applied as a magnetic nanosorbent for the removal of carbamazepine (CBZ) from the wastewater samples. The prepared adsorbent was characterized by various modern surface and microstructure analyzing methods. Several operating parameters affecting the removal efficiency of the CBZ including sample pH, amount of sorbent, initial concentration and adsorption time were investigated and adjusted. However, under the optimal conditions, the PPy–CS–Fe3 O4 MNCs showed prominent removal performance compared to the bare Fe3 O4 magnetic nanoparticles. According to the results, the PPy–CS–Fe3 O4 MNCs could eliminate the CBZ from water medium with an efficiency of 94.5% in the 25 min. In contrast, it took about an hour to remove 65% of the CBZ using bare Fe3 O4 magnetic nanoparticles. The experimental results revealed that the CBZ sorption on the PPy–CS–Fe3 O4 MNCs was fitted well with the pseudo-second-order kinetic model (R 2 = 0.9901). Moreover, the adsorption model was in accordance with the Langmuir isotherm with the adsorption capacity of 121.95 mg g −1 . It was found that PPy–CS–Fe3 O4 MNCs could be frequently applied for CBZ removal up to five times without noticeable decrease in its adsorption efficiency. The adsorption results established the high potential of synthesized MNCs as a robust and promising adsorbent for water treatment. Graphical Abstract: ga1 Highlights: PPy–CS–Fe3 O4 MNC was synthesized for the removal of CBZ from wastewater. The adsorption model was in accordance with the Langmuir isotherm with the adsorption capacity of 121.95 mg g −1 . Kinetic of adsorption followed the pseudo-second-order model. CBZ was taken over a wide pH range regardless of the adsorbent surface charge. π-π electron donor-acceptor interaction and H-bonding led to the adsorption of CBZ on the PPy–CS–Fe3 O4 MNC.